2009
DOI: 10.2116/analsci.25.1167
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Studies of Uranium(VI), Plutonium(IV) and Americium(III) from Nitric Acid Using the Bi-functional Carbamoyl Methyl Sulfoxide Ligands

Abstract: The extraction behavior of new bi-functional ligands containing sulfoxide and amide groups viz. N,N′-dibutyl carbamoyl methyl phenyl sulfoxide (L1) and N,N′-dibutyl carbamoyl methyl benzyl sulfoxide (L2) towards the U(VI), Pu(IV) and Am(III) ions from nitric acid was studied. Both of these extractants showed appreciable extractions for U(VI) and Pu(IV) from 1 to 9.5 M nitric acid concentrations. Am(III) did not show an appreciable extraction under the conditions studied. The species extracted from a nitric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Uranium can be dissolved in either an acid or alkali solution; however nitric acid is probably the most commonly used reagent for dissolving uranium ore samples. 2,[13][14][15] Thus, development of technologies for the determination of uranium isotopic ratio ( 235 U/ 238 U) in uranyl nitrate is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Uranium can be dissolved in either an acid or alkali solution; however nitric acid is probably the most commonly used reagent for dissolving uranium ore samples. 2,[13][14][15] Thus, development of technologies for the determination of uranium isotopic ratio ( 235 U/ 238 U) in uranyl nitrate is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction behavior of new bi-functional ligands containing sulfur and amide groups towards the U(VI) ion from nitric acid was studied and reported [19][20][21][22][23][24] . Other reports are related to P based extractants used for U extraction [25][26][27][28][29] and our previous extraction studies on U extraction was developed and reported [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have proposed alternatives to TBP, [3][4][5] among them monoamide derivatives [6][7][8][9] exhibit high potential as well as carbamides which have been studied very recently. [10][11] Another approach consists of designing multifunctional molecules, various multi-functional compounds have shown promising properties, for example, iminomethylenediphosphonic acids (phosphorus and nitrogen functions) [12] or amidosulfoxide structures (sulfur and nitrogen functions) [13] have been proposed for uranium extraction and purification from diluted or concentrated nitric acid solutions. Taking into account the potential of this approach, a new series of N, P bifunctional extractants was patented and showed excellent properties in nitric media in terms of affinity for uranium extraction.…”
Section: Introductionmentioning
confidence: 99%